57 Prompt Assessment of Cardiac Status Following Preload Reduction Using 12 Lead ECG. (31st May 2014) - Lee, Eveline; Fraser, Alan; Yousef, Zaheer
Abstract : Background: Preload reduction during haemodialysis causes change in cardiac filling and contractility. This can be accurately assessed using standard echocardiography. We hypothesise that simple ECG parameters approximate Echo derived measurements and can be used as an initial tool. Methods: Thirty subjects (Age 59 ± 18 years, 35% female, LVEF 64 ± 6%, LVEDVI 38 ± 14, LVMI 119 ± 62) on maintenance haemodialysis (median duration 26 months) consented to take part in the study. Standard echocardiography and twelve lead ECG were performed immediately before and after a mid week session of haemodialysis (mean duration 4 h). Echocardiography images were analysed offline using dedicated software, Echopac. ECGs were acquired using standard paper speed of 25mm/s and measured using a calliper and averaged over 12 leads. QRS amplitude was chosen as surrogate marker of systolic contractile function. Tend P/PQ ratio was used to approximate early to late diastolic filling (E/A) ratio.Continuous variables were reported as mean ± standard deviation, categorical data were reported as percentages. Statistical analyses were performed using SPSS 20, paired t-test was used for comparison, 2-tail p value of <0.05 was considered significant. Results: The median weight loss following dialysis was 1.6 ± 1.3 kg (95% CI 1.1–2.1, p < 0.001). Average basal septal and lateral systolic velocity increased by 1.1 ± 2.3 cm/s (p = 0.03) and this is reflected in the increase of QRS amplitude by 0.18 ± 0.30 mV (p < 0.01). Diastolic filling pressure was reduced, E/A dropped by 0.15 ± 0.28 (p = 0.01) and Tend P/PQ dropped by 0.18 ± 0.6 (p = 0.16) despite no change in heart rate. The following figures show good linear correlation of Echo and ECG parameters. Conclusion: Preload reduction resulted in increased contractile function despite reduced filling pressure. Simple ECG measurements approximate the change in Echo parameters and can be used to identify potentially high risk group of dialysis patients.